ЭКОЛОГИК ТАРҒИБОТ ВА АТРОФ-МУҲИТ МУҲОФАЗАСИ - Байжанов, Қ.Қ.; Аметов, Я.И. (FAN va JAMIYAT, 2024)
As a result of extensive development of agriculture in the Central Asian region, uncontrolled use of land and water, the Aral Sea began to dry up. The ecological system of the land, animal and plant life in the area has been seriously challenged. The meteorological conditions of the regions also affect the negative change of the ecological climate. The main reason for the emergence of such unfortunate situations is the lack of environmental knowledge and skills among construction, ice-breaking experts and even management staff. Therefore, raising environmental education and upbringing among the general population is considered an important task today. Conducting ecological promotion authors work on a systematic approach construction is taken into account.